The influence of [H2SiO4]2- from mineral admixtures on the hydration process of tricalcium silicate: a DFT study - Dong, Haotian; Cheng, Jie; Feng, Yuhao; Liu, Houjun (Frontiers in Materials, 2023)
Mineral admixtures are increasingly being employed in the concrete production to replace cement, thus reducing carbon dioxide emissions. However, the leaching of silicon can exert a significant influence on the cement hydration process. In this study, density functional theory was used to study the influence of [H2SiO4] 2-on the adsorption and dissociation of water on C3S surface in the initial hydration process. The results demonstrate that [H2SiO4] 2-can promote the dissociation of water molecules around it. This is mainly due to the fact that the two non-hydroxylated O atoms of the [H2SiO4] 2-can adsorb the dissociated H from water molecules, thus preserving more active ionic O sites on the C3S surface, thereby promoting the dissociation of water molecules. The charge transfer and bonding mechanisms of the adsorption of [H2SiO4] 2-with its hydration shell were also calculated.This work provides an atomic level understanding of the influence of aluminum phase from mineral admixture on the initial hydration of cement and also offers certain assistance for the widespread application of mineral admixtures.